Analisis Open Journal System Lembaga Ilmu Pengetahuan Indonesia - Sri Wulan; Sensusiyati Sensusiyati; Rochani Nani Rahayu (Perpustakaan Nasional, 2022)
An analysis of the Open Journal System (OJS) published by the Indonesian Institute of Sciences 2016-2020 was carried out, against the background of the growing development of OJS. The analysis aims to determine: a) The number of OJS issued by LIPI; b) Number of OJS that have received SINTA accreditation from the Ministry of Research and Technology/BRIN; c) Frequency of issue of OJS; d) Most publishers; e) Number of articles published 2016-2020. The data source is a journal located on the https://ejournal.lipi.go.id/ site. The study used a descriptive method, and data collection was carried out by noting the title of the journal, frequency of publication, description of the contents of the journal, the first year it was published, the level of accreditation of the SINTA journal, and the number of articles. The results showed that 25 OJS titles had been published, and the most were in the social and humanities field (9 journals). OJS is at least an engineering field (4 titles). The Sinta 2 accreditation is in the top position, but there is no SINTA 1 accreditation. The highest frequency of publication is twice a year, the number of articles is 1,631 titles, namely the field of biology, 447 titles, social humanities 773 titles, engineering 191 titles, and earthly 220 titles. It is concluded that OJS LIPI has 25 titles, with the number of social and humanities journals occupying the first place, it is necessary to improve the quality of journals from SINTA 2 to SINTA 1.